Situational diagnosis of the Institutional Research Ethics Committees in Social Security in Peru - Herrera-Añazco, Percy (2022)
Background: Although the Instituto de Evaluación de Tecnologías e Investigaciones en Salud (IETSI) has promoted the formation of Institutional Research Ethics Committees (IRECs) in the social security of Peru (EsSalud), there may be perfectible aspects. The characteristics of the IREC of EsSalud and its members during 2021 are described. Material and Methods: A descriptive and observational study was carried out using a secondary database. IREC members were surveyed using a virtual form created by IETSI. 114 members belonging to 18 EsSalud networks were included. Results: 52.6% of the participants were male, the mean age was 50.6 ± 11.9 years, and 42.1% had a scientific role. In 38.8% of the IREC were evaluated more than five clinical trials in the last two years and 72.2% more than five observational studies in the same period. The members reported limitations for holding virtual meetings or supervisions, lack of time to carry out their tasks due to the high workload and the need for training on research methodology and biostatistics. Conclusion: it is necessary to improve the administrative support and the training plan for the members of the IREC of EsSalud, to achieve methodological, ethical, and regulatory competencies that ensure an improvement in the processes of evaluation and ethical monitoring of human research.